Public participation: healthcare rationing in the newspaper media - Audun Brendbekken; Bjarne Robberstad; Ole F. Norheim (BMC, 2022)
Abstract Background It is impossible to meet all healthcare demands, but an open and fair rationing process may improve the public acceptability of priority setting in healthcare. Decision-making is subject to scrutiny by newspaper media, an important public institution and information source for discussions about rationing. In Norway, healthcare rationing has been subject to public debate both before and after the establishment of "The National System for Managed Introduction of New Health Technologies within the Specialist Health Service" (New Methods) in 2013. Aim To describe and assess the development of the public debate on Norwegian healthcare rationing through three cases in print media. Methods We purposively sampled Norwegian newspaper articles between 2012 and 2018 concerning three reimbursement decisions in the Norwegian system. The reimbursement decisions were ipilimumab (Yervoy, n = 45) against metastatic melanoma, nivolumab (Opdivo, n = 23) against non-small cell lung cancer, and nusinersen (Spinraza, n = 68) against spinal muscular atrophy. Cases were analysed separately using the qualitative method of systematic text condensation. Results Our analysis highlighted four common themes-money, rationales, patient stories, and process-and a unique theme for each case. Ipilimumab was uniquely themed by rationing rejection, nivolumab by healthcare two-tiering, and Spinraza by patients' rights. We found wide media deliberation among a multitude of stakeholders in all cases. Perceptions of rationing were found to be chiefly aligned with previous empirical research. We found that the media reported more frequently on opposition to rationing compared to findings from previous studies on Norwegian healthcare decision-making attitudes. We think this was influenced by our selection of cases receiving extraordinary media attention, and from media sources being subject to political communication from special interest groups. Conclusion We observed that the introduction of New Methods institutionalised Norwegian healthcare rationing and isolated the public debate into conversations between stakeholders and decision makers outside the political sphere. The findings from these three extraordinary debates are not generalisable and should be seen as a stakeholder learning opportunity regarding media coverage and engagement with expensive specialist healthcare decision-making in Norway.